Endoscopic surgery combined with titanium mesh for infantile solitary orbital myofibroma: a case report - Jiang, Ligang; Jiang, Xin; Wu, Wencan; Jiang, Fangzheng (Frontiers in Pediatrics, 2025)
BackgroundTo report the clinical features, misdiagnosis process and minimally invasive treatment experience of endoscopy combined with titanium mesh in a 3-year-old infant with isolated orbital myofibroma, and to discuss the key points of differential diagnosis and treatment strategy.Case reportA 3-year-old male patient presented with progressive swelling of the left lower eyelid for 1 month, without eye redness, eye pain, diplopia, or ocular motility disturbance. There was no significant family history or past medical history. Ophthalmic examination revealed visual acuity of 0.5 in the right eye and 0.6 in the left eye. Swelling was observed in the right face and the lower eyelid, with a palpable mass that was well-mobile, firm in texture, and non-tender. The ocular positions were normal with regular motility, while anterior segment examination and fundoscopy showed no abnormalities. Imaging information indicated a well-defined oval mass (1.5 cm × 2.1 cm) in the infraorbital foramen area of the anterior wall of the right maxillary sinus, accompanied by erosion and destruction of the anterior wall of the maxillary sinus. Because of the imaging features and frozen section were highly similar to those of schwannoma, both presenting as well-defined spindle cell tumors, a misdiagnosis of “right orbital schwannoma” was identified. However, that misdiagnosis did not alter the surgical approach. We performed endoscopic microsurgery to achieve precise resection and avoid damaging normal tissues. Meanwhile, a titanium mesh was implanted to reconstruct the orbital bone defect, restoring its anatomical structure and function. Intraoperative frozen section showed a spindle cell tumor, which tended to be diagnosed as schwannoma. Postoperative immunohistochemistry indicated SMA (+), Calponin (+), Ki-67 (+, proliferation index of 20%), Desmin (−), S-100 (−), CD34 (−), CK (−), leading to the final diagnosis of infantile solitary orbital myofibroma.ConclusionInfantile orbital myofibroma is clinically rare and frequently misdiagnosed as schwannoma, which requires immunohistochemical and molecular genetic testing for definitive diagnosis. Endoscopic minimally invasive techniques demonstrate significant advantages in preserving normal tissues. Titanium mesh can effectively reconstruct orbital bone defects and restore anatomical structure and function. However, long-term follow-up is required to monitor its potential impact on maxillofacial development in infants and young children.